2010
DOI: 10.1007/s11060-010-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

The detection of CMV pp65 and IE1 in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is a highly lethal brain tumor affecting children and adults, with the majority of affected individuals dying from their disease by 2 years following diagnosis. Other groups have reported the association of cytomegalovirus (CMV) with GBM, and we sought to confirm these findings in a large series of patients with primary GBM from our institution. Immunohistochemical analysis of paraffin embedded tissue sections was performed on 49 newly diagnosed GBM tumors, the largest series repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 44 publications
6
112
2
4
Order By: Relevance
“…Recently, an onco-accessory function of CMV has also been described in a mouse model of glioblastoma using murine cytomegalovirus infection (11). More importantly, CMV antigens and nucleic acids have been detected in histologic sections of GBM but not in surrounding healthy tissue (12)(13)(14)(15)(16)(17)(18). Although these histologic findings have been disputed (19)(20)(21), more recent studies have confirmed the presence of CMV sequences in malignant cells (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an onco-accessory function of CMV has also been described in a mouse model of glioblastoma using murine cytomegalovirus infection (11). More importantly, CMV antigens and nucleic acids have been detected in histologic sections of GBM but not in surrounding healthy tissue (12)(13)(14)(15)(16)(17)(18). Although these histologic findings have been disputed (19)(20)(21), more recent studies have confirmed the presence of CMV sequences in malignant cells (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 80% of the patients had detectable HCMV DNA in their peripheral blood. Lucas et al (2011) performed IMH of HCMV proteins on 49 paraffin-embedded tissue sections of GBM tumours, the largest series reported to date. They confirmed the presence of HCMV pp65 in 25/49 (51%) and IE1 in eight/49 (16%) of these tumours.…”
mentioning
confidence: 99%
“…Lucas et al found that CMV pp65 and IE1 expression was mostly in the cytoplasm of GBM samples, and that CMV specific T cells were able to recognize and lyse GBM cells that were infected with CMV in the laboratory. 51 The immunotherapeutic strategies for targeting CMV include adoptive T cell transfer and vaccine approaches. Adoptive T cell therapy has been mostly described using CMV-specific T cells from patients that are ex-vivo expanded.…”
Section: As Immunotherapeutic Targetmentioning
confidence: 99%